2021
DOI: 10.1002/adfm.202103384
|View full text |Cite
|
Sign up to set email alerts
|

Tendency of Gap Opening in Semimetal 1T′‐MoTe2 with Proximity to a 3D Topological Insulator

Abstract: Monolayer (ML) 1T′-MoTe 2 has attracted intensive interest as a fascinating quantum spin Hall (QSH) insulator. However, there are two critical aspects impeding its exploration and potential applications of QSH effects. One is its semimetallic feature with a negative band gap, leading to nontrivial edge channels annihilated by the bulk states. The other is its fabrication always accompanied by a mixed phase of 1T′ and 2H. Based on first-principles calculations, it is shown that the large work-function differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…[ 177 ] Our group has recently proposed a plausible road for the opening of the band gap in a monolayer of 1Tʹ‐MoTe 2 through the formation of a 1Tʹ‐MoTe 2 /Bi 2 Te 3 vdW‐type heterostructure and by utilizing the SOC proximity effect. [ 174 ] Our theoretical studies have revealed that strong interlayer interactions and the prominent charge transfer at the interface are the origins of the SOC proximity effect and the enhanced intrinsic SOC in such a heterostructure. The enhanced intrinsic SOC is the prerequisite for the band gap opening, and the calculated band gap for a monolayer of 1Tʹ‐MoTe 2 is ∼40 meV.…”
Section: Intriguing Topological Phenomena Related To Bi2te3‐based Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 177 ] Our group has recently proposed a plausible road for the opening of the band gap in a monolayer of 1Tʹ‐MoTe 2 through the formation of a 1Tʹ‐MoTe 2 /Bi 2 Te 3 vdW‐type heterostructure and by utilizing the SOC proximity effect. [ 174 ] Our theoretical studies have revealed that strong interlayer interactions and the prominent charge transfer at the interface are the origins of the SOC proximity effect and the enhanced intrinsic SOC in such a heterostructure. The enhanced intrinsic SOC is the prerequisite for the band gap opening, and the calculated band gap for a monolayer of 1Tʹ‐MoTe 2 is ∼40 meV.…”
Section: Intriguing Topological Phenomena Related To Bi2te3‐based Filmsmentioning
confidence: 99%
“…Reproduced from Ref. [174] Copyright 2021, John Wiley and Sons. (C) STM surface morphology and STS superconducting energy gap in Bi 2 Se 3 films grown on superconducting NbSe 2 substrates.…”
Section: Intriguing Topological Phenomena Related To Bi2te3‐based Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, compared to the Δ CF , the Δ SOC varies slightly near the characteristic zone, indicating the lattice strain plays a minor role in modulating Δ SOC . Since the SOC could be tuned by doping or forming hetero‐structure, [ 56–58 ] one would expect to realize a triple‐degenerated VBM (i.e., VB1, VB2, and VB3 coinciding in energy) in Mg 3 Sb 2 through combined efforts of strain engineering and compositional adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…Mater. 2023, 33, 2300154 could be tuned by doping or forming hetero-structure, [56][57][58] one would expect to realize a triple-degenerated VBM (i.e., VB1, VB2, and VB3 coinciding in energy) in Mg 3 Sb 2 through combined efforts of strain engineering and compositional adjustment.…”
Section: Discussion On Strain Engineeringmentioning
confidence: 99%